2020
DOI: 10.1002/ange.202003081
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between Diazo Compounds and Hypervalent Iodine(III) Reagents

Abstract: Site‐selective “cut and sew” transformations employing diazo compounds and hypervalent iodine(III) compounds involve the departure of leaving groups, a “cut” process, followed by a reorganization of the fragments by bond formation, a “sew” process. Bearing controllable cleavage sites, diazo compounds and hypervalent iodine(III) compounds play a critical role as versatile reagents in a wide range of organic transformations because their excellent nucleofugality allows for a large number of unusual reactions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…19 Our group [20][21][22][23][24][25][26][27] is engaged in the novel method development using hypervalent iodine(III) chemistry. [28][29][30][31][32][33][34][35] Despite a personal account and a review on NH-sulfoximines which was reported by the Bull group and the Luisi group, [36][37][38] no review has been published, to the best of our knowledge, discussing the chemistry of iodonitrene. We are motivated to provide a concise minireview, highlighting iodonitrene and its application in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Our group [20][21][22][23][24][25][26][27] is engaged in the novel method development using hypervalent iodine(III) chemistry. [28][29][30][31][32][33][34][35] Despite a personal account and a review on NH-sulfoximines which was reported by the Bull group and the Luisi group, [36][37][38] no review has been published, to the best of our knowledge, discussing the chemistry of iodonitrene. We are motivated to provide a concise minireview, highlighting iodonitrene and its application in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[11] More recently,t he groups of Bonge-Hansen [12] and Gaunt [13] demonstrated applications of the linear hypervalent iodine reagents in nucleophilic halogenations and in am ethionine bioconjugation of peptides and proteins,respectively. [14] Considering that this unusual class of hypervalent iodine reagents can serve as an electrophilic diazomethyl source,we anticipated that silyl enol ethers derived from ketones could be suitable nucleophiles.Infact, silyl enol ethers are known to react with hypervalent iodine reagents and deliver a-substituted carbonyl compounds. [15] Herein, we present the successful execution of this concept for an ew synthesis of bdiazocarbonyl compounds.T he synthetic method is general, simple to perform, relatively fast, occurs at room temperature and does not require atransition-metal catalyst (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%